Transition metal doped CeO2 for photocatalytic removal of 2-chlorophenol in the exposure of indoor white light and antifungal activity - Qamar, M. Tariq; Iqbal, Shahid; Aslam, M.; Alhujaily, Ahmad; Bilal, Anum; Rizwan, Komal; Farooq, Hafiz Muhammad Umer; Sheikh, Tahir Ali; Bahadur, Ali; Awwad, Nasser S.; Ibrahium, Hala A.; Almufarij, Rasmiah S.; et al. (Frontiers in Chemistry, 2023)
Besides natural sunlight and expensive artificial lights, indoor light can play a significant role in activating a catalyst for photocatalytic removal of organic toxins from contaminated water. In the current effort, CeO2 has been modified with Ni, Cu, and Fe through doping methodology to study the removal of 2-chlorophenol (2-CP) in the illumination of 70 W indoor light. The successful doping was confirmed with a minor shift and size reduction in the diffraction pattern of cubic CeO2. The solid-state absorption spectra revealed higher absorbance of Cu-doped CeO2 whereas a lower absorption response was observed for Ni-doped CeO2. An interesting observation regarding the lowering of direct band gap energy of Fe-doped CeO2 ( 2.8 eV) and an increase in Ni-doped CeO2 ( 3.2 eV) in comparison to pristine CeO2 ( 3 eV) was noticed. The process of e-– h+ recombination in the synthesized photocatalysts was also investigated through photoluminescence spectroscopy. The photocatalytic studies revealed the greater photocatalytic activity of Fe-doped CeO2 with a higher rate ( 3.9×10-3 min.-1) among all other contestants. Moreover, kinetic studies also revealed the validation of the Langmuir-Hinshelwood kinetic model (R2=0.9839) while removing 2-CP in the exposure of indoor light with a Fe-doped CeO2 photocatalyst. The XPS analysis of Fe-doped CeO2 was also performed to confirm the presence of peaks corresponding to Fe2P3/2 and Fe2P1/2.